Stock market and economic growth in Eastern Europe - María Asuncíon Prats Albentosa; Beatriz Sandoval (Kiel Institute for the World Economy (IfW), 2016)
A developed financial system is essential in a market economy. This paper studies the importance of the development of financial markets in general, and the stock market in particular, from the review of existing literature in the area of the relationship between financial development and economic growth, and especially, the link between the stock market and economic growth. Through an empirical analysis for six countries in Eastern Europe (Bulgaria, Slovakia, Hungary, Poland, Czech Republic and Romania) it is tried to show the link between the stock market development and economic growth in these countries from 1995 to 2012 in order to explain the transition processes, from communist to market economies, which began with the fall of the Berlin Wall in 1989. The results show evidence of Granger causality between economic growth variables and financial market variables.
Keywords: F43; O16; G2; 330; economic growth; stock market; financial markets; financial development